2010
DOI: 10.1145/1721933.1721953
|View full text |Cite
|
Sign up to set email alerts
|

Computer science teacher preparation is critical

Abstract: In this paper, we report on the research and recommendations of the CSTA (Computer Science Teachers Association) Teacher Certification Task Force, addressing the crisis in computer science teacher preparation and certification. This paper will address the importance of computer science as a scientific discipline, and provide a brief discussion of the relevant research and current existing certification models Primarily, however, this paper focuses on the Task Force's recommended models for teacher preparation … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
28
0
7

Year Published

2011
2011
2020
2020

Publication Types

Select...
3
3
3

Relationship

0
9

Authors

Journals

citations
Cited by 59 publications
(37 citation statements)
references
References 10 publications
2
28
0
7
Order By: Relevance
“…The answer to this question is multi-faceted. The nature of CT as described above places this way of thinking and problem-solving into the higher levels of Bloom's taxonomy (Bloom et al 1956, Gal-Ezer andStephenson 2010). Besides encouraging higher level thinking in students, there are several practical reasons for integrating CT into science and mathematics classrooms.…”
Section: Smp#1mentioning
confidence: 99%
“…The answer to this question is multi-faceted. The nature of CT as described above places this way of thinking and problem-solving into the higher levels of Bloom's taxonomy (Bloom et al 1956, Gal-Ezer andStephenson 2010). Besides encouraging higher level thinking in students, there are several practical reasons for integrating CT into science and mathematics classrooms.…”
Section: Smp#1mentioning
confidence: 99%
“…Mishra and Koehler [47] have added knowledge about technology to this model. [41] as well as experiences in Informatics [22] have shown that teacher education is a very critical factor for the learning success of the students. The didactical knowledge of Mathematics teachers has turned out to be a very dominant factor e.g.…”
Section: Bm: Preconditions\teacher Qualification\teacher Education Dmmentioning
confidence: 99%
“…CS as optional subject (16) Negative perceptions of CS (11) Low student enrolment (10) No CS (7) Problems at governmental level (5) Diverse capabilities of students (2) Lack of trained teachers (23) Perceived same as ICT (17) Curriculum difficulties (10) Lack of teaching resources (7) No quality evaluation (5) Trends…”
Section: Problemsmentioning
confidence: 99%
“…Some comparisons of computing at schools on international level have been made [13]. Initiatives to support CS, new curricula, new forms of support for teachers, and course materials are being developed [2,4,8,10,18]. For many years, the ACM/CSTA Model Curriculum for K-12 CS has served as a national standard in the U.S., Canada, Philippines, and Australia for pre-college CS education.…”
Section: Introductionmentioning
confidence: 99%